Surveying instruments and technology - Nadolinets, Leonid; Akhmedov, Daulet; Levin, Eugene (Boca Raton : Taylor & Francis, CRC Press, 2017)
"With the advent of GPS/GNSS satellite navigation systems and Unmanned Aerial Systems (UAS) surveying profession is nowadays facing its transformative stage. Written by a team of surveying experts, Surveyor's Instruments and Technology gives surveying students and practitioners profound understanding of how surveying instruments are designed and operating based on surveying instrument functionality. The book includes the required basic knowledge of accurate measurements of distances and angles from theoretical principles to advanced optical, mechanical, electronic and software components for comparative analysis. Readers are presented with basic elements of UAS systems, practical interpretation techniques, sensor components, and operating platforms. Appropriate for surveying courses at all levels, this guide helps students and practitioners alike to understand what is behind the buttons of surveying instruments of all kinds when considering practical project implementations. "--Provided by publisher.
chapter 1 Introduction -- chapter 2 Levels -- chapter 3 Theodolites -- chapter 4 Electronic Distance Measurer (EDM) -- chapter 5 Total Stations -- chapter 6 Global Navigation Satellite Systems (GNSS) -- chapter 7 Obtaining and Processing Unmanned Aerial Vehicle (UAV) Data for Surveying and Mapping.
Keywords: Geodesy; Geospatial data; Surveying -- Instruments